The involvement of ADAM10 in acantholysis in mucocutaneous pemphigus vulgaris depends on the autoantibody profile of each patient. (1st May 2020) - Ivars, M.; España, A.; Alzuguren, P.; Pelacho, B.; Lasarte, J.J.; López‐Zabalza, M.J.
Summary: Background: Acantholysis in pemphigus vulgaris (PV) may be triggered by desmoglein (Dsg) and non‐Dsg autoantibodies. The autoantibody profile of each patient results in distinct intracellular signalling patterns. Objectives: Based on our previous findings, we aimed to elucidate whether PV acantholysis in a mouse model may be mediated by activation of a disintegrin and metalloproteinase 10 (ADAM10). Methods: We used three PV‐IgG fractions from different patients containing high or low levels of anti‐Dsg1 and anti‐Dsg3 antibodies, and the presence or not of anti‐desmocollin (Dsc) antibodies, using a passive transfer mouse model of PV. Results: Although all of the PV‐IgG fractions produced suprabasal acantholysis, only those containing anti‐Dsg1/3, but not anti‐Dsc2/3 antibodies, induced ADAM10 activation in a Src‐dependent way, and an increase in the epidermal growth factor (EGF) receptor ligands EGF and betacellulin (BTC). In contrast, the presence of anti‐Dsc2/3 antibodies, in addition to anti‐Dsg1/3, triggered earlier and ADAM10‐independent epidermal detachment, with no increase in EGF and BTC, which was associated with an earlier and more intense acantholysis. Conclusions: All PV‐IgG fractions produced suprabasal acantholysis, but our results reveal that depending on the levels of anti‐Dsg antibodies or the presence of non‐Dsg antibodies, such as anti‐Dsc, more severe cell–cell epidermal detachment will occur at different times, and in an ADAM10‐dependent manner or not. Acantholysis in these different groups of patients with PV may be a consequence of the activation of specific intracellular mechanisms downstream of Autoantibodies binding to Dsg or non‐Dsg proteins, and therefore more specific therapeutic approaches in PV should be used. What's already known about this topic? Suprabasal acantholysis in pemphigus vulgaris (PV) may be triggered by both desmoglein (Dsg) and non‐Dsg autoantibodies. The autoantibody profile of each patient is associated with a distinct intracellular signalling pattern. What does this study add? In patients with PV with anti‐Dsg3 and anti‐Dsg1, but not anti‐desmocollin (Dsc)3 antibodies, ADAM10 activation is induced in an Src‐dependent way, together with an increase in the epidermal growth factor receptor (EGFR) ligands EGF and betacellulin. The presence of anti‐Dsc3 antibodies triggers an earlier and ADAM10‐independent acantholysis, without increasing EGFR ligands, and is associated with more severe epidermal detachment. Lower levels of anti‐Dsc3 antibodies are associated with less severe acantholysis. What is the translational message? In some patients with PV, the severity and the timing for cell–cell detachment seem to depend on the level of anti‐Dsg1/3 antibodies, although other as yet uncharacterized antibodies may also participate. These patients with PV would exhibit inhibition of acantholysis by Src, ADAM10, EGF and EGFR inhibitors. In other patients, the presence of non‐Dsg antibodies, such as anti‐Dsc2/3, would produce an earlier and more severe ADAM10‐independent suprabasal acantholysis.